Structural Characterization and Immunomodulatory Activity of a Novel Polysaccharide From Lycopi Herba - Zhang, Wuxia; Hu, Yihua; He, Jiaqi; Guo, Dongdong; Zhao, Jinzhong; Li, Peng (Frontiers in Pharmacology, 2021)
Lycopi Herba has been broadly used as a traditional medicinal herb in Asia due to its ability to strengthen immunity. However, it is still obscure for its material basis and underlying mechanisms. Polysaccharide, as one of the most important components of most natural herbs, usually contribute to the immunomodulatory ability of herbs. Here, we aim to detect polysaccharides from Lycopi Herba and examine their potential immunomodulatory activity. A novel polysaccharide (LHPW) was extracted from Lycopi Herba and purified by DEAE-52 cellulose chromatography and G-100 sephadex. According to physicochemical methods and monosaccharide composition analysis, LHPW was mainly composed of galactose, glucose, fructose, and arabinose. NMR and methylation analysis indicated that LHPW was a neutral polysaccharide with a backbone containing →3,6)-β-D-Galp-(1→, →4)-β-D-Galp-(1→ and →4)-α-D-Glcp-(1→, with the branches of →1)-β-D-Fruf-(2→ and →6)-α-D-Galp-(1→. Immunological tests indicated that LHPW could activate macrophages RAW264.7 and promote splenocyte proliferation. This study discovered a novel polysaccharide from Lycopi Herba and showed it was a potential immunomodulator.